help with rearrange equation

just want to ask which is correct way of doing **ax + by + x = 0**

example is y = 2x + 8

y **-y **= 2x **-y **+ 8 **(basically take away y both sides)**

0 = 2x -y + 8

or

y **- 2x -8** = 2x + 8 **- 2x - 8 (instead of taking y away, take 2x + 8 away both sides)**

-2x + y - 8 = 0

which one is correct?

thanks for your help in advance.

Re: help with rearrange equation

Quote:

Originally Posted by

**yuenj01** just want to ask which is correct way of doing **ax + by + x = 0**

example is y = 2x + 8

y **-y **= 2x **-y **+ 8 **(basically take away y both sides)**

0 = 2x -y + 8

or

y **- 2x -8** = 2x + 8 **- 2x - 8 (instead of taking y away, take 2x + 8 away both sides)**

-2x + y - 8 = 0

which one is correct?

thanks for your help in advance.

The first option was surely far more straightforward? Although either method is correct.

Re: help with rearrange equation

Quote:

Originally Posted by

**Quacky** The first option was surely far more straightforward? Although either method is correct.

that is what i was thinking. in da exams, is it acceptable?

Re: help with rearrange equation

If you multiply either solution by -1 on both sides, you'll find that they're exactly the same.

Re: help with rearrange equation

Quote:

Originally Posted by

**yuenj01** just want to ask which is correct way of doing **ax + by + x = 0**

Do you mean ?

Quote:

Originally Posted by

**yuenj01** example is y = 2x + 8

y **-y **= 2x **-y **+ 8 **(basically take away y both sides)**

0 = 2x -y + 8

or

y **- 2x -8** = 2x + 8 **- 2x - 8 (instead of taking y away, take 2x + 8 away both sides)**

-2x + y - 8 = 0

which one is correct?

thanks for your help in advance.

Either is correct at Quacky has pointed out. The convention is usually to make the leading term (**ax**) positive so in this case you would take y from sides but it would be a very petty marker who enforced that